2010
DOI: 10.1007/s10573-010-0004-x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of nano-aluminium during combustion of composite solid propellant mixtures

Abstract: Nano-aluminium particles are produced using the electric wire explosion process in an inert atmosphere at our institute. This paper reports the characterization of nanoaluminium particles in combination with other solid propellant ingredients for their thermal and combustion behaviour. High-heating-rate hot-stage microscopic experiments are performed with different mixtures of propellant ingredients. The effects of addition of nano-aluminium versus micron-sized aluminium in the middle lamina of sandwiches are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…The slope of the straight line, adjusted for image magnification of camera, yielded the burning rate as illustrated in Figure 5. The error estimation in the measurements of the burning rate was found to be within AE 3 % as reported [24]. At least 90 % of the steady state burning rate data was tested for repeatability, variations within 5 % is acceptable [25].…”
Section: Propellant Burning Rate Measurementsupporting
confidence: 59%
“…The slope of the straight line, adjusted for image magnification of camera, yielded the burning rate as illustrated in Figure 5. The error estimation in the measurements of the burning rate was found to be within AE 3 % as reported [24]. At least 90 % of the steady state burning rate data was tested for repeatability, variations within 5 % is acceptable [25].…”
Section: Propellant Burning Rate Measurementsupporting
confidence: 59%
“…From the above, two factors are already investigated by authors which can be related to compare the present study with other researchers' outcomes, namely, combustion pressure and parent aluminium particle size. It was noticed that the possibility of aluminium agglomeration and its size is relatively low at high pressure and with large parent aluminium sizes of micro-aluminised propellants (Anand et al, 2013), whereas the same trend is observed for pressure effect of the nano-aluminized propellants (Jayaraman, 2010(Jayaraman, /2011). In the present study, 450 nm aluminum particles are used which restricts the agglomeration factor range within 24-46.…”
Section: The Condensed Combustion Products Analysismentioning
confidence: 74%
“…Post-burning analysis of solid propellants containing nano-particles and micro-particles shows that the nano-aluminized propellant has higher combustion efficiency than a micron-aluminized propellant; also, the pressure effect on the chemical composition, size, and morphology of the combustion residues is significant (Galfetti et al 2007). Recently, authors reported aluminium agglomerate size distribution of around 1-5 μm from propellants (Jayaraman, Chakravarthy, & Sarathi, 2011) and sandwiches (Jayaraman, Chakravarthy, & Sarathi, 2010) using experiments which contains nano-aluminium particles with the size of 50 nm produced from electrical wire explosion and also the micron-sized aluminium particles agglomeration in propellants using both experimental and modelling studies (Anand, 2013). These studies are carried out by maintaining the distance between burning surface and quench distance as constant.…”
mentioning
confidence: 99%
“…It was noticed that the possibility of aluminium agglomeration and its size is relatively low at high pressure and with large parent aluminium sizes of micro‐aluminised propellants, whereas the same trend is observed for pressure effect of the nano‐aluminized propellants. In the case of Jayaraman et al , the wide range of agglomeration factor is due to the smaller‐ sized nano‐aluminium and its wide operating pressure ranges. On the contrary, agglomeration factor is in concise range of variation due to short pressure range and also relatively high due to low pressures .…”
Section: Resultsmentioning
confidence: 99%
“…Also, the pressure effect is significant as compared to chemical composition, particle size, and morphology of the combustion residues. Recently, authors reported the quenched surface of nano‐aluminized sandwiches shows relatively smaller aluminium agglomerates than micron‐sized aluminium . The resultant particle sizes of nano‐aluminium agglomerates is in the range of 1–5 μm, which indicates a higher rate of agglomeration than with micron‐sized aluminium, but these sizes are small relative to the agglomerates of latter .…”
Section: Introductionmentioning
confidence: 99%